Negative Roots

Algebra Level 2

4 × 9 = ? \large \sqrt { -4 } \times \sqrt { -9 } = \, ?

-6 5 6 36

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

18 solutions

Discussions for this problem are now closed

Dominick Hing
Oct 4, 2014

Relevant wiki: Simplifying Expressions with Radicals - Basic

Using complex numbers , we rewrite the expression in terms of i i like so: i 4 × i 9 i\sqrt { 4 } \times i\sqrt { 9 } . This leads to i 2 × 36 { i }^{ 2 }\times \sqrt { 36 } or 6 -6 .

Despite your first instinct, the solution is not 36 \sqrt { 36 } . The answer is not 36 \sqrt { 36 } because you can only multiply the numbers under the radical if they are both positive, as explained here: do square roots always multiply?

Moderator note:

Yes, you're absolutely right. The equation A × B = A × B \sqrt A \times \sqrt B = \sqrt{A\times B } is only true when A , B 0 A,B\geqslant 0 .

For those who are considering "branch cuts" and want to argue that "it could also be +6 if we chose the different branch", unfortunately we cannot choose a different branch when we are evaluating the expression. For example, we do not say that " i + i = 0 i + i = 0 because for the second i i we interpret it as i -i instead". Similarly, we do not say that i × i = 1 i \times i = 1 because for the second i i we interpret it as i -i instead".

Actually, if you consider all the possible solutions to the square roots, the answer could be 6 or -6:

sqrt(-4) = -2i or 2i sqrt(-9) = -3i or 3i

thus, making all possible combinations: 2i* 3i = -6 -2i* 3i = 6 2i -3i = 6 -2i -3i = -6

The same result would be obtained if one multiplied both numbers before resolving the square root:

sqrt(-4)* sqrt(-9) = sqrt(36) = 6 or -6

therefore the answer marked as correct should be changed to 6 or -6.

Alan Wilson - 5 years, 7 months ago

no ,before radical sign there is no sign,that means only+ hence -6 is the only one answer & the2nd formula in ur soln. is valid only for non negative nos.

Arindam Marik - 5 years, 6 months ago

The square root function is defined only for positive numbers. And even if it was defined on negative numbers then the square root should be a positive number, but square root of a negative number is a complex number and complex numbers can't be compared with zero.

Adrian Neacșu - 5 years, 7 months ago

.... any complex number different from 0 has N Nth roots ... the correct answer is "6 or -6"

Migu El - 5 years, 6 months ago

squareroot of -4 is+-2i,but when we use the root sign that means only +.....the ans will be only -6.

Arindam Marik - 5 years, 6 months ago

Challenge Master:

I agree, the answer is -6 but the statement that

A × B = A × B \sqrt{A} \times \sqrt{B} = \sqrt{A \times B}

is only true when A,B \geq 0 is not convincing. The better explanation uses the order of precedence of operations. Rewriting the equation as

( 4 ) 1 / 2 × ( 9 ) 1 / 2 (-4)^{1/2} \times (-9)^{1/2} and using order of precedence means we should evaluate inside the parenthesis before we do the multiplication. This gives

( 4 ) 1 / 2 × ( 9 ) 1 / 2 = 2 i × 3 i = 6 i 2 = 6 (-4)^{1/2} \times (-9)^{1/2} = 2i \times 3i = 6i^{2} =-6

Michael Short - 5 years, 6 months ago

That's a great explanation!

I wasn't attempting to provide a solution, but just explaining a common misconception that many people had.

Calvin Lin Staff - 5 years, 6 months ago

√-4√-9 = ±√-4(-9) = ± √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6 There is something missing in your solution.

Michael Garcia - 5 years, 6 months ago

You can only combine radicals when the terms under the radical are both positive

Abdur Rehman Zahid - 5 years, 5 months ago

When multiplying radicals, you must multiply the numbers OUTSIDE (O) the radicals AND then multiply the numbers INSIDE (I) the radicals.

Michael Garcia - 5 years, 5 months ago

If it has the same root, multiplying radicals,,,you can just get the product of the radicands, and don't forget a square root of any number are + and -.

Michael Garcia - 5 years, 5 months ago

@Michael Garcia I don't get what you're saying.Can you please be more clear?

Abdur Rehman Zahid - 5 years, 5 months ago

@Abdur Rehman Zahid It is in the rule of multiplying radical numbers that "When multiplying radicals, you must multiply the numbers OUTSIDE (O) the radicals AND then multiply the numbers INSIDE (I) the radicals." and square root of a number, it could be positive and negative.

Michael Garcia - 5 years, 5 months ago

So the complex number i is positive? I don't think so

Howard Phillips - 5 years, 2 months ago

Errado. Não existe um número real. Não se pode misturar números reais com imaginários e ter como resposta um número real.

Walterson Almeida - 5 years, 7 months ago

So i is positive ??? I don't think so.

Howard Phillips - 5 years, 2 months ago

I completely agree with this. The only thing I would recommend is to clarify from the beginning over which field were working on. If it is the real numbers, the operations are not defined. If it is the complex numbers, then the results you present hold.

Dikki Gs - 5 years, 7 months ago

but \sqrt{36} = 6 and -6 the real answer is +6 and -6

Osmar Lozano - 5 years, 7 months ago

This is a common misconception. \sqrt{36} is 6, by definition . The solution of x^2=36 is x=±6, which can also be written as x=±\sqrt{36}. We express that there are two values with the ±, but the \sqrt itself only gives the positive root.

This is just a definition - you might not like it, but it's just how we've decided to do it. It's convenient because it means that \sqrt is a function that takes one answer and gives one answer.

David Williamson - 5 years, 7 months ago

Wrong. The concept of square root, in latin, is: "radix quadratum 9 aequalis 3" (the side of a square area 9 is equal to 3). In this way, there's no negative side of a square.

When we have x^2=y => x=+/-sqrt(y)

Walterson Almeida - 5 years, 7 months ago

Ya man, this site is stupid, even if the square root of -9 is equal to -3 and the square root of -4 is equal to -2 then it would have to be positive 6, but then it is absolutely impossible to have a square root of a negative number so that doesn't matter anyways.

Lukas Ladas - 5 years, 6 months ago

@Lukas Ladas @Lukas Ladas Firstly,it seems you aren't familiar with complex numbers.Go read about them.Secondly,square root of -9 is not -3,it is 3 i 3i ,similarly for -4.The square root of a negative real number is not a real number;it is an imaginary number

Abdur Rehman Zahid - 5 years, 5 months ago

check out the definition of sqrt buddy

Jelson Chacko - 5 years, 7 months ago

How come you turn 6i into -6? Can you simply turn imaginary numbers into negative real numbers?

Allan Lima - 5 years, 7 months ago

@Allan Lima They did not turn 6i into -6,they turned 6i^2 into -6,because i^2=-1

Abdur Rehman Zahid - 5 years, 5 months ago

In my opinion, there are two solution of this question, not one! I think you cannot just write as i.sqr(4) x i.sqr(9)

It must be [(±i).sqr(4)] x [(±i).sqr(9)] = [(±i).(±2)] x [(±i).(±3)] ⇒ There are only two possible solutions in all combinations ; 6 & -6.

Burak Yalçıntaş - 5 years, 6 months ago

@Burak Yalçıntaş No,-i√4=-2i,not i√4,which is equal to +2i.Similarly for i√9.Square Root of a number is defined as the positive number which when squared gives that number

Abdur Rehman Zahid - 5 years, 5 months ago

I cannot write all these symbols with my keyboard. I agree with your analysis but the final result is i squared (-1) times root 36. Root 36 is + or -6 therefore the final result is - or +6.

Monette Pahlawan - 5 years, 6 months ago

no,when we use the root sign that means only +,e.g. square root of 25 is+-5,but if we write 25 under root,that equals only+5

Arindam Marik - 5 years, 6 months ago

That is not true. If you were ever taught that your teacher was wrong. Every time I learned ANYTHING about square roots they always said the +/-. All of my text books have a note about it too, even when speaking about functions.

Patricia Edwards - 5 years, 6 months ago

@Patricia Edwards no, i dont agree, √4=+2,but square root of 4=+/-2.....note the difference.....actualy ,squqre root of 4=+/- √4=+/-2. only √4=+2....√4 never means (-2)

Arindam Marik - 5 years, 6 months ago

this is correct in a way but it is not the proper answer the way to solve this is u solve both of the radicals leading to 2i x 3i=6i since i=-1 u could argue the answer is -6 but the proper answer is 6i

Keiver Santos - 5 years, 6 months ago

2i*3i=6i^2, not 6i

Abdur Rehman Zahid - 5 years, 5 months ago

√-4√-9 = ±√-4(-9) = ± √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6

Michael Garcia - 5 years, 6 months ago

Sqrt(-4).sqrt(-9) = sqrt(-4.-9)=sqrt(36) = 6

Faisal Basha - 5 years, 5 months ago

yes u are right

Gourab Roy - 5 years, 5 months ago

Hi Dominick! Why can't sqrt 36 be -6

Balaji Subramoniam - 5 years, 4 months ago

but i can also say that -4*-6=36, actually it's both 6 and -6

Gourab Roy - 5 years, 4 months ago

-4^.5 times -9^.5 = x (-4^.5)^2 times (-9^.5)^2 = x^2 -4 times -9 = x^2 36=x^2 X=6, -6

Caleb DeLisle - 5 years, 3 months ago

I believe you cannot use a radical number with the minus sign

Shanna Elbaze - 5 years, 1 month ago

Why isn't it 6i squared?

Jason Townsend - 5 years ago

But the square root of 4 is 2, and the square root of 9 is 3. Both are negative, so -2 x -3 is 6, right???

Sammy Carryer - 5 years ago

But either way you're still left with 2 possible answers -1×6 or -1×(-6)

Alex Harman - 5 years ago

It really could be either guys and gals and here is your explanation. To simplify radicals that have negative numbers you must first factor out the negative using I. This leaves you with i square roots of 4 times i square roots of 9. Simplified down you are left with i^2 × square of 36. Now square root of 36 is both 6 and -6. According to the cycle of imaginary numbers i^2= -1. So you could have 6×-1=-6 or -6x-1=6. The solution stating either is incorrect. It is in fact both.

Nathan McDowell - 5 years ago

Wrong. We can't mix Real numbers with Imaginary numbers and as result a Real number.

Walterson Almeida - 5 years, 7 months ago

@Walterson Almeida They are multiplying two Complex numbers,not one real number and one complex number

Abdur Rehman Zahid - 5 years, 5 months ago

(√-4) (√-9) ≈ √[(-4) (-9)] = √36 = 6 ... I think :p

Sorin Diaconescu - 5 years, 4 months ago

is there a square root of a negative number? what negative number multiplied by itself is equal to another negative number? i see this pointless.

Ariel Dominguez - 5 years, 7 months ago

You can't take the square root of a negative number, it's impossible. Think, what number times itself equals -4? -2? Nope, -2 squared is 4. No number times itself can be negative

Lennin McMahon - 5 years, 7 months ago

you talk about real number, we talk about imaginary number. it's completely different.

Achmad Arrizal - 5 years, 7 months ago

I agree with Lennin Mc Mahon

Vito Opeña - 5 years, 7 months ago

The real answer is 6i

Ricardo Perez Arellano - 5 years, 6 months ago

the problem is that you guys try to solve complex field equation with high school tools, which are true only for real numbers.

In the real numbers field, we have an order - for every two numbers x, y it holds x < y ,x > y or x = y and the three are mutually exclusive. In particular, we can order numbers by their relation with 0 - this is the well known partition into positive (x > 0) and negative (x < 0) numbers. Under these definitions, the expression sqrt(x) for a real non negative number x is defined to be the real non negative number y s.t. y^2 = x. It can be proven (in calculus courses) that for each non negative number x there is one and only one such a number y. But for a negative number there is no such a number, since for any non zero real number y, either if y>0 or y<0, y^2>0. this is true only for the real numbers.

But this is not true for complex numbers.

A complex number is a vector or point in the Real-Imaginary plain. For the complex field, we don't have an order; Think about it, which number is bigger - 0 or i? i or -i? the last two are just two vectors pointing to opposite sides. There is no order. so if we have more than one complex number for which the equation y^2 = x holds, then there is no reason or way to prefer one number over the other. Hence we can't talk about THE root of a complex number, only about all possible numbers that suffice the equation. There is a general formula how to extract them, but for our current needs it's enough to claim that for the nth root there are exactly n different numbers, no more, no less.

In particular, the expression "sqrt(-4)" is not defined over the real field, and in the complex field it's an abuse of notations (since as I explained there is no THE root in the complex field), relating the complex numbers y for which y^2 = -4. Those numbers are y=2i and y=-2i (since we know that there are exactly 2 different numbers that suffice the equation, and these 2 number suffice the equation and different from each other). Similarly "sqrt(-9)" is of no meaning either, and in the complex field it can relate to 3i or -3i. therefore, "sqrt(-4) sqrt(-9)" is not defined over the real numbers, and in complex numbers it can be any of the combinations of "roots" of -4 with "roots" of -6, that is:

2i 3i = -6,

2i (-3i) = 6,

(-2i) 3i = 6,

(-2i) (-3i) = -6

so the answer is either 6 or -6.

Lesson to life: don't abuse notations!

Matan Holzer - 5 years, 6 months ago

Yes looking at this problem I thought the same. You are 100% correct. Sort of. This is a principal square root=it will never have a negative root. (Sqrt.)36 = 6 (Sqrt.) 0= 0 Not -0

Giacomo Liberato - 5 years, 5 months ago

Positive and negative sign has nothing to do with 0

Prabalpreet Singh - 5 years, 1 month ago

There is a difference between x=√-9 and x^2=-9

Abdur Rehman Zahid - 5 years, 5 months ago

Very well said...

Randy Keck - 5 years, 6 months ago

So why couldn't you pick 2 answers? I knew -6 and 6 both were correct 😑

Andreas Deman - 5 years, 5 months ago
Alec Camhi
Jun 26, 2015

4 9 = i 4 ( i 9 ) = i 2 36 = 1 ( 6 ) = 6 \sqrt { -4 } \sqrt { -9 } \\ =\quad i\sqrt { 4 } (i\sqrt { 9 } )\\ =\quad { i }^{ 2 }\sqrt { 36 } \\ =\quad -1(6)\\ =\quad \boxed { -6 }

The square root of 36 could be either 6 or -6. So, is 6 also correct? (i^2 x -6 = 6)

Franz` Herz - 5 years, 7 months ago

36 \sqrt{36} is not square root of 36. It is principal square root of 36. Principal square root is always a positive number.

Kien Nguyen - 5 years, 7 months ago

More like it's never negative. 0 = 0 \sqrt 0 = 0

Whitney Clark - 5 years, 6 months ago
Gian Sanjaya
Sep 24, 2015

Let me post one thing about this:

  1. The definition of x \sqrt{x} for x R + x \in R^+ is the value of a POSITIVE real number y such that y 2 = x y^2=x .

  2. i = 1 , 0 = 0 i = \sqrt{-1}, \sqrt{0}=0

  3. The definition of x \sqrt{-x} for x R + x \in R^+ is i i times the value of a POSITIVE real number y such that y 2 = x y^2=x .

This should be a very basic definition and thus 4 9 = ( 2 i ) ( 3 i ) = 6 \sqrt{-4}\sqrt{-9} = (2i)(3i) = \boxed{-6}

Notes:

  1. You can raise a complex number x to the power of non-integer real number only if x is a real number, although I'm not sure that we can raise negative real number to the power of irrational number.

  2. This problem is clearly stated and obviously correct. I would also say that it doesn't break the posting rules and guidelines.

  3. Most identities for exponentials, on most cases, are unable to be used for complex field. Example: e 2 π i = 1 e^{2\pi i}=1 , but e π i = 1 e^{\pi i} = -1 , so ( e 2 π i ) 0.5 e π i (e^{2\pi i})^{0.5} \neq e^{\pi i} .

  4. However, ( z a ) n = z a n (z^a)^n = z^{an} for z C , a , n Z , z 0 z \in C, a, n \in Z, z \neq 0 still holds. Also for z R + , a , n R z \in R^+, a, n \in R (although I'm not really sure with this one).

Every1 confused here should see your post.

Nick Zafiridis - 5 years, 6 months ago
Ed Barrett
Nov 6, 2015

This is incorrect... the answer is there is no answer... there is no square root to a minus number and according to BIDMAS you should square root the numbers before multiplying. Since you can't square root the numbers (this is because squaring a minus number becomes a positive number), you can't reach a solution

You are unfamiliar with imaginary numbers?

Paul Alberti-Strait - 5 years, 6 months ago

I gave the answer as -6 because I knew that only the principal roots are taken here. However, the pair of - 6 and +6 will be a better answer!

Nah, I think the right answer is better.

Whitney Clark - 5 years, 6 months ago
Erm Mie
Oct 28, 2015

Using simple factoring 4 9 = ( 4 × 1 ) × ( 9 × 1 ) = 2 × 3 1 × 1 = 6 × ( 1 1 ) = 6 \text{Using simple factoring}\\\sqrt{-4} \sqrt{-9}\\=(\sqrt{4} \times \sqrt{-1}) \times (\sqrt{9} \times \sqrt{-1})\\=2 \times 3 \sqrt{-1}\times \sqrt{-1}\\=6 \times (-1^1)\\=\boxed{-6}

Tnx boss. it's the most easiest ans i got here. :)

Milkan Uddin - 5 years, 7 months ago

√-4√-9 = ±√-4(-9) = √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6

Michael Garcia - 5 years, 6 months ago

√-4√-9 = ±√-4(-9) = √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6

Michael Garcia - 5 years, 6 months ago
David Bloom
Sep 27, 2015

I think all the arguing is based off of one misunderstanding of math, and a second of how to solve the mystery. Their Misunderstanding: The reason you use + or - in an equation is because of the X term underneath the radical, you don't know if it is a positive or a negative so you need to adjust for that somehow. However, in this problem we know what the number is and therefore do not need the.plus or minus. 2: When solving the problem, the simplest and least complex way is to simplify at the end and not sooner. So you take the square root of both first and end up with 3ii*2i = 6i^2 which implies that it is = -6

i feel whole argument and confusion is around treatment of numbers. If we treat numbers on daily calculation (taught in kindergarten days) than -a * -b = +ab than answer should be +6 but if we use concept of complex numbers of i^2= -1 than answer should be 6i rather than -6 because we are not taking root of i^2 but replacing it by its corresponding value. But since correct answer should be one so mathematicians need to standardize how -ve sign should be treated and should be taught likewise since begining to child wheather it come in their nursery grade or 2nd 3rd grade in whatever grade educationist feel fit to teach young mind.And young mind has sufficient ability to learn correct things in less time than wrong things in name of simple and than rectifying to correct knowledge in their later years...

Manan Aggarwal - 5 years, 8 months ago
Pratik Borikar
Nov 13, 2015

It's pretty simple.

sqrt(-4) sqrt(-9)=(i sqrt(4) ) * (i sqrt(9)) Therefore, its (i^2) sqrt(36) which is -1 (+/- 6)

So the answer is +6 or -6

The options are incorrectly labelled. :P

√36=+6 becuase it is defined to give the positive value.-√36=-6,not +√36

Abdur Rehman Zahid - 5 years, 5 months ago

(-4)^1/2 is 2i. (-9)^1/2 is 3i. (2i)(3i)=(2)(3)(-1)=-6

√-4√-9 = ±√-4(-9) = √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6

Michael Garcia - 5 years, 6 months ago

√-4√-9 = ±√-4(-9) = √36 = ±6 or √-4√-9 = ± [2i(3i)] = ± 6i^2 = ± 6(-1) = ± 6

Michael Garcia - 5 years, 6 months ago
Bheshaj Dewangan
Apr 20, 2016

What if both the numbers are equal??? sqrt((-8)^2) = +8 or -8

Ryan Wallentine
Dec 31, 2015

The answer is -6 and not 6.

Please note that the square root of a number is always positive from the definition of the square root. The only reason we ever have to add a plus/minus sign when dealing with square roots is to preserve a function dealing with variables. note that y=x^2 is not the same as sqrt(y)=x. Hence, in order to preserve all values of the function, we would have to add a plus/minus before sqrt(y). In other words, y=x^2 if and only if x=±sqrt(y).

However, sqrt(4) is not equal to -2. sqrt(4)=2. That's it. If you don't believe me, go to Wolfram Alpha and type "sqrt(4)=-2" into the search box. It will return false. You can also type in sqrt(-4)sqrt(-9)=6 and it will return false.

Ruby Syuukyoku
Nov 23, 2015

The squared root of a negative number is the same as the positive number just with i to symbolize it isn't real (squared root of -1 is equal to i) So -4 becomes 2i and -9 becomes 3i (2i)(3i) makes 6i^2 i^2 is -1 as the squared root of anything times itself is the number w/o squared root. So -6 is the final answer after turning 6i^2 into (6)(-1)

Arthur Rizzo
Nov 21, 2015

although i understand and agree with the solution: -6, because of i squared. Still what the matter of multipling negative radicals as if they where "regular" radicals?

@Arthur Rizzo Because you can only combine radicals when both terms are positive

Abdur Rehman Zahid - 5 years, 5 months ago
Leonardo Villete
Nov 20, 2015

1: sqrt{-4}= sqrt{4} x sqrt{-1} 2: sqrt{-9}=sqrt{9}x sqrt{-1}

sqrt{-4} x sqrt{-9} = sqrt{4} x sqrt{-1} x sqrt{9} x sqrt{-1} = = 2 x 3 x sqrt{-1} x sqrt{-1} = =6 x sqrt{-1}^2 = =6 x (-1) = -6

Lanie Roberts
Nov 14, 2015

So, with pemdas, we have to do exponents first (which radicals technically are) so you end up with 2i x 3i which gives 6i^2 which is -6

Grace Bismark
Nov 8, 2015

√-4 = 2i

√-9 = 3i

i^2 = -1

Therefore: (√-4)(√-9) =

2i * 3i = 6i^2 =

6(-1) = -6

Raghav Dua
Oct 30, 2015

The easiest thing would be to start by converting both the numbers into their simplest forms, i.e., their complex forms (OH THE IRONY). We know that:

i = sqrt (-1)

so sqrt (-4) = sqrt (4) * sqrt (-1) => 2i

similarly sqrt (-9) => 3i

now the expression becomes: 2i*3i

2 * 3 = 6, but also:

i * i = sqrt (-1) * sqrt (-1) = sqrt (-1) ^ 2 = -1

Thus: 6 * -1

=> -6 !!

Zorror Verdas
Oct 28, 2015

root -4 x root -9 => -1 {root(4x9)} => -1 root 36 => -6

Yeah but two (-) = to a (+) my enemies enemies is my friend so you would do sqt root of 4 and 9 multiply it and it would give you +6 but a sqt root of a number is always +or- cuz 2x2=4 but -2x-2=4 also so it +or-6 the answer

Dylan Lebel - 5 years, 7 months ago

@Dylan Lebel No,square root of a number is positive

Abdur Rehman Zahid - 5 years, 5 months ago

When I was doing this I was told to use J as the square root of -1 so J4 was the square root of -1 4 so the equasion should be J4 J9 therefore 6 being the answer?

David Lanckmans - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...